2017
DOI: 10.1080/10400435.2016.1265024
|View full text |Cite
|
Sign up to set email alerts
|

Connected cane: Tactile button input for controlling gestures of iOS voiceover embedded in a white cane

Abstract: Accessibility of assistive consumer devices is an emerging research area with potential to benefit both users with and without visual impairments. In this article, we discuss the research and evaluation of using a tactile button interface to control an iOS device's native VoiceOver Gesture navigations (Apple Accessibility, 2014). This research effort identified potential safety and accessibility issues for users trying to interact and control their touchscreen mobile iOS devices while traveling independently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In presenting the results of the literature review an overview of the corpus of papers found in the search will first be provided in order to offer a detailed context for the review findings; particularly in relation to access needs, age range, technologies and intended purpose of technology use .18 papers involved users with sensory impairments as their primary user group. Of these, three involved blind users [21,20,33]; seven involved visually impaired users; three involved both blind and visually impaired users [17,18,20]); two involved deaf users [29,31]; two involved deaf or hard of hearing users [24,28]and one involved hard of hearing users [22]. 14 papers involved users with learning disability as their primary user group.…”
Section: Review Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In presenting the results of the literature review an overview of the corpus of papers found in the search will first be provided in order to offer a detailed context for the review findings; particularly in relation to access needs, age range, technologies and intended purpose of technology use .18 papers involved users with sensory impairments as their primary user group. Of these, three involved blind users [21,20,33]; seven involved visually impaired users; three involved both blind and visually impaired users [17,18,20]); two involved deaf users [29,31]; two involved deaf or hard of hearing users [24,28]and one involved hard of hearing users [22]. 14 papers involved users with learning disability as their primary user group.…”
Section: Review Methodsmentioning
confidence: 99%
“…15 papers reported focusing on re-designing existing technologies. For example one study involving users with sensory impairments focused on designing a tactile button interface that could control the native Voice-Over Gesture navigations of IOS devices [18]. There were nine intended purposes of the technologies that the projects were developing: communication, daily living, education, employment, health, accessing information, leisure, safety and travel.…”
Section: Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ye et al 2014) recognize the obstacles along with estimating cane pose using Visual Range Odometry (VRO) method. (Batterman et al 2017) connected a tactile button to the handle of the white cane for accessing iOS navigation apps such as Blind Square and Seeing Eye, where the input chosen by the blind users is spoken loudly by the VoiceOver app to assist them in making correct selections. The benefit of adopting this approach is accessing the smartphone without holding it.…”
Section: Functionalitymentioning
confidence: 99%
“…Owing to the everincreasing blind and visually impaired population, assistive devices have constantly been in a huge demand for recent years [6]. For instance, as a traditional mobility aid, the white cane is the most popular among blind and visually impaired people (VIP) [7]. However, the performance is far from satisfactory as common white canes indicate limited information of obstacle position.…”
Section: Introductionmentioning
confidence: 99%